2023
DOI: 10.1021/acs.energyfuels.2c03054
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Asphaltene Subfractions A1 and A2 in Different Solvents from the Perspective of Molecular Dynamics Simulations

Abstract: The aggregation behavior of model molecules of asphaltene subfractions A1 and A2 dissolved in heptane, toluene, and tetrahydrofuran (THF) were studied using molecular dynamics simulations. The proposed asphaltene molecular models are based on previously studied structures with two new models, including a highly aromatic model with a prominent island-type molecule and another molecule with a prominent archipelago-type architecture. The aggregation mechanisms in toluene, THF, and heptane solvents were studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…For instance, Figure a illustrates the formation of asphaltenes clusters in heptane, a typical bad solvent for asphaltenes, where the molecules tend to aggregate into a few larger clusters. It was found that the dipole moment showed a significant decrease with the increase in the number of molecules in the asphaltene aggregates. , In another case, Figure c portrays the dispersion of asphaltene molecules in toluene, a typical good solvent for asphaltenes, resulting in a relatively higher dipole moment. To enhance the understanding of the asphaltene aggregates, a detailed examination was conducted on the average dimensions and quantity of asphaltene clusters.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Figure a illustrates the formation of asphaltenes clusters in heptane, a typical bad solvent for asphaltenes, where the molecules tend to aggregate into a few larger clusters. It was found that the dipole moment showed a significant decrease with the increase in the number of molecules in the asphaltene aggregates. , In another case, Figure c portrays the dispersion of asphaltene molecules in toluene, a typical good solvent for asphaltenes, resulting in a relatively higher dipole moment. To enhance the understanding of the asphaltene aggregates, a detailed examination was conducted on the average dimensions and quantity of asphaltene clusters.…”
Section: Resultsmentioning
confidence: 97%
“…Using different asphaltene molecular models, including models for two subfractions of asphaltenes, A1 with a rigid core that tends to aggregate easily, A2 with higher flexibility in structure and better solubility in toluene, a highly aromatic island model, and archipelago-type model, the aggregation behavior was studied. The asphaltene aggregates were observed in various solvents even at low concentrations. , Further investigations revealed that the simulated system exhibited size distribution profiles similar to the gel permeation chromatography (GPC) experimental analyses of asphaltene samples in tetrahydrofuran (THF). , Interestingly, Villegas et al showed that the dipole moment of asphaltene aggregate tends to be zero when the number of molecules in the aggregate increases. They pointed out that such dipole moment cancellation could be the fundamental reason for the dispersion of the asphaltene aggregate. , Kunieda et al studied a light oil model including paraffinic, naphthenic, and aromatic compounds and found that the weak hydrogen bonding between water and aromatics can induce a self-accumulation of aromatics at the oil–water interface. With the development of digital oil models, it has become possible to describe crude oils covering all the fractions, including the light fractions, heavy fractions, and asphaltenes for light crude oils, and saturates, aromatics, resins, and asphaltenes for heavy crude oils. ,,, The Hildebrand solubility parameters of polyaromatic hydrocarbon compounds have been evaluated based on MD simulations .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…THF is of great importance in petroleomics since it prevents the metals Ni and V from being adsorbed in the GPC column . Also asphaltene aggregates seem not to break down in this medium according to theoretical, and experimental studies, even at low concentration of 25 ppm . Considering the results of the previous works, the choice of solvent and the choice of pore size of the columns seems to be the most important parameters that influence the retention times and profile shape.…”
Section: Optimization Of the Gpc Conditions (Traditional Detectors)mentioning
confidence: 92%
“…Hence, the benefits from fractionation to understand the mechanisms behind silver complexation were demonstrated, as these differences were not visible through the analysis of the whole asphaltene solution. Molecular dynamics has also been used to evaluate the aggregation mechanism of asphaltene and their A1/A2 subfractions, providing information about aggregate size distribution. ,, Key findings from these theoretical studies include the observation of no disaggregation of the asphaltenes in THF and the fact that THF, as a highly polar solvent, is more likely to limit the absorption of asphaltenes onto the stationary phase, which again proved the interest of using such solvent to study asphaltenes stability in a state as native as possible.…”
Section: Gpc Hyphenation With Icp-msmentioning
confidence: 99%